2016
DOI: 10.5958/2394-4196.2016.00002.9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonography in Prediction of Technical Difficulties in Laparosopic Cholecystectomy - Clinical Research

Abstract: Background: Laparoscopic surgery widely, known as single incision laparoscopic cholecystectomy (LC), has been proved as the gold standard surgical technique and is now considered the treatment of choice as well as preferred surgical technique in cholecystectomy. The use of laparoscopic technique in cholecystectomy is widely used for cholelithiasis patients. An abdominal ultrasonography (USG) often precedes this surgery and can verify the diagnosis, as well as help in showing possible complications during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Impacted stones at Hartmann's pouch makes dissection difficult because of difficulty in holding GB at Hartmann's pouch. Husain et al (24) found that stone size more than 1 cm was a significant factor for difficult and very difficult LC with P value <0.05.…”
Section: Discussionmentioning
confidence: 97%
“…Impacted stones at Hartmann's pouch makes dissection difficult because of difficulty in holding GB at Hartmann's pouch. Husain et al (24) found that stone size more than 1 cm was a significant factor for difficult and very difficult LC with P value <0.05.…”
Section: Discussionmentioning
confidence: 97%
“…The forceps, with large jaws, must be used to grasp or suture the GB wall to extract or cut off a part of the GB wall, and then firmly pull it. Thickened GB is a risk factor for difficult LC 2,18 and conversion to open cholecystectomy [7][8][12][13] . The thickened GB had the highest predictive value in predicting the difficulty of LC; additionally, it was a significant predictor in the prediction model.…”
Section: Discussionmentioning
confidence: 99%